EFFECTIVENESS OF THE SECOND MOTOR VEHICLE NAME TRANSFER DUTY EXEMPTION PROGRAM IN 2022 (STUDY AT TECHNICAL IMPLEMENTATION UNIT REGION I PALU) - Nugraha, Rahadian; M., Mustainah; Suasa, Suasa; Riadi, Slamet; Hasanuddin, Hasanuddin (Penerbit Lafadz Jaya, 2024)
This study aims to determine the Effectiveness of the Second Motor Vehicle Name Reverse Duty Exemption Program in 2022 (Study at the Technical Implementation Unit of Region I Palu). This study used a method with descriptive qualitative data. The research location is located in the Technical Implementation Unit of Region I Palu The theory used in this study is the theory proposed by Dunncan (in steers). The informants in this study amounted to 5 (five) people. The data obtained in this study are from observations, interviews, and documentation. Data analysis methods are Data Collection, Data Condensation, Data Presentation, and Conclusion Drawing / Verification. The results of this study show that the effectiveness of the Second Motor Vehicle Name Duty Exemption Program in 2022 (Study at the Technical Implementation Unit of Region I Palu) has not been running effectively, this is due to the non-achievement of the effectiveness indicators used in this study, such as the Integration indicator, seen from the aspects of: First, Coordination. From the results of the study, it is known that from the aspect of internal and external coordination has not been effective. Second, Socialization. As for those related to the implementation of socialization with taxpayers, it has been carried out effectively. Adaptation indicators, seen from the aspect: First, the resources of the tax collector apparatus are inadequate. Second, the Tax Collection Facility, especially those related to the Application of the kamputerisai system, has not been optimal so that the management of tax revenue data and information has not been effective. Similarly, field operational support facilities are not yet available as needed, the Third Tax Collection Mechanism, where it is known that at the time of the Waiver of Motor Vehicle Tax Fines and the exemption of Motor Vehicle name return duties for the management of UPTB Region I Palu tax collection has not been optimal because it does not have a set Standard Operating Procedure (SOP) and still uses SOPs as usually regulated in regulations.